2010
DOI: 10.3109/13625187.2010.534515
|View full text |Cite
|
Sign up to set email alerts
|

Contraception, reproductive health and pregnancy outcomes among women exposed to intimate partner violence in Nigeria

Abstract: Though causal inference cannot be drawn due to the cross-sectional design, the study has important implications for incorporation of IPV detection and management in initiatives aimed at improving women's reproductive health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 26 publications
7
65
1
Order By: Relevance
“…In other climes, studies have provided substantial evidence that exposure to spousal violence is related to pregnancy termination [34][35][36] . In one of the few studies conducted in Nigeria, it was found that women exposed to spousal violence had higher likelihood of miscarriages, induced abortions and stillbirths 37 . Against the backdrop of women's poor sexual and reproductive health, it is expected that more studies will be conducted in the country to further determine the relationship between spousal violence and pregnancy termination.…”
Section: Further Literaturementioning
confidence: 99%
“…In other climes, studies have provided substantial evidence that exposure to spousal violence is related to pregnancy termination [34][35][36] . In one of the few studies conducted in Nigeria, it was found that women exposed to spousal violence had higher likelihood of miscarriages, induced abortions and stillbirths 37 . Against the backdrop of women's poor sexual and reproductive health, it is expected that more studies will be conducted in the country to further determine the relationship between spousal violence and pregnancy termination.…”
Section: Further Literaturementioning
confidence: 99%
“…Globally, between 10% -69% of women experience Intimate Partner Violence (IPV), the most common form of domestic violence, with higher figures in low income countries. This coupled by the well documented physical, mental and reproductive health consequences of IPV (WHO, 2002;Campbell, 2002;Emenike, Lawoko, & Dalal, 2008;Okenwa, Lawoko, & Jansson, 2011;Gage, 2005), and higher frequency of healthcare seeking in this special group, when contrasted with the general population (Hegarty, 2006), is indicative that such violence may account for a significant portion of women's total health burden. In support of this notion, a recent systematic review of the literature by the World Health Organization (WHO) of over 80 countries including low, middle and high income countries concluded that Intimate Partner Violence (IPV) against women is a global health problem of epidemic magnitude (WHO, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Though the epidemiology of IPV has over the past decade received increasing attention in the research in lowincome countries, the issue of IPV screening in healthcare is not yet sufficiently addressed [1] [3] [4]. In Uganda, the context for the current study, nationally representative data places the prevalence of physical, sexual and emotional abuse with women as victims at 25%, 20% and 33% respectively, and up to 70% of the population justify wife abuse for scenarios where a wife defies from normative roles expected of her in the house hold (e.g.…”
Section: Study Contextmentioning
confidence: 99%
“…The World Health Organization (WHO) places the global prevalence of IPV against women at between 3% -38% [1] with higher figures in low income countries. A substantial proportion of physically assaulted women sustain injuries ranging in severity from bruises to fractured bones, exhibit symptoms of depression, anxiety and post-traumatic stress disorder, indulge in health risk behaviors including unhealthy feeding habits, substance abuse, alcoholism and suicidal behaviors and encounter reproductive health complications including terminated and undesired pregnancies and child loss during infancy [1]- [4]. In low income countries, poverty, inadequate health services and a culture of acceptance for violence against women [1] [3] [4] further aggravate the problem.…”
Section: Epidemiology Of Intimate Partner Violencementioning
confidence: 99%
See 1 more Smart Citation